A New Simplified Stain Extracted From The Petals of Kujarat Tea Flovers ( Hibiscus Subdariffa ) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In tile present study a ne~T stain has been e}:.1racted for U18 first time from the potals of Kujarat tea flowers. Bolt;' watery and alcoholic extracts were prepared and exatnined for their ability to stain different human parasitic protozoa and helminths ova ( in preserved and fresh!y passed stool samples ).The results of staining with Kujarat stain proved to be highly efficient when compared with routine stains ( such as iodine and. trichrome). In addition to that no differences vere observed between the watery and alcoholic extractsJ so the present work recommended the use of watery solution of stain ( in saline ) at the concentration of ( 8% wt.! vol. ) for both routine and teaching purposes. The dried petals can be easi1y obtained from the local markets with a cheep price and then the stain can be sasily prepared at any time.